Time-kill assay of N-(2-Bromoethyl)-7-chloroquinilin-4-amine (ACP 4A) with fungistatic activity against Aspergillus fumigatus - Dayang Fredalina Basri,; Kuek, Sze Yee; Jacinta Santhanam,; Mohd Asyraf Shamsudin,; Nur Hanis Zakaria,; Jalifah Latip,; Nurul Izzaty Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Six pyrano[2,3-c]pyrazole-3-carboxylate and quinoline derivatives (ACP 1A, ACP 1B, ACP 1C, ACP 1D, ACP 2A and ACP 4A) synthesized and screened for antimicrobial activity against two selected Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), three Gram-negative bacteria (Klebsiella pneumonia, Pseudomonas aeruginosa, and Escherichia coli), two yeast strains (Candida albicans and Candida glabrata) and two filamentous fungi (Aspergillus niger and Aspergillus fumigatus) using agar well diffusion method. Minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) of the compounds were determined using broth microdilution and streak plate method, respectively. Time-kill assay (TKA) analysis of N-(2-bromoethyl)-7-chloroquinilin-4-amine (ACP 4A) was subsequently conducted throughout the 24 h incubation period against A. fumigatus. Only ACP 4A was chosen for the evaluation of TKA analysis because the broth dilution assay confirmed that it is the most potent compound with antifungal activity. E. coli was the only one found to be susceptible to the ACP 4A compound at 20 and 30 mg mL-1 with an inhibition zone value of 15.00 ± 0.00 and 19.00 ± 0.00 mm, respectively. MIC values of ACP 4A compound against S. aureus and C. albicans were 800 µg mL-1. A. niger and A. fumigatus exhibited the highest susceptibility towards ACP 4A with the same MIC value (200 µg mL-1). ACP 4A showed fungicidal effect against C. glabrata with the same MIC and MFC values at 800 µg mL-1. From TKA analysis, ACP 4A at 1 × MIC and 2 × MIC did not show fungicidal activity against A. fumigatus. In conclusion, ACP 4A has the potential to be developed as a fungistatic (non-fungicidal) antifungal agent, which is an advantage compared to other known fungicidal compounds, particularly in patients with a healthy immune system.